Summary and Prospect of Steel Slag Treatment Technology at the “Double Carbon” Goal - Yidang HAO; Huigang WANG; Long WU; Guibo QIU; Changsheng YUE; Ben PENG (Kuangchan zonghe liyong)
This is an article in the field of metallurgical engineering. As a solid waste produced in the process of steelmaking, the steel slag has the characteristics of large output, high temperature, complex chemical composition and poor stability. The resource utilization rate of steel slag in China is less than 30%, resulting in the waste of valuable resources contained in steel slag. The stockpiling of a large number of steel slag will also occupy a large amount of land and cause soil and water pollution. The resource utilization of steel slag is closely related to its treatment technology. Based on this, this paper briefly introduces the primary treatment processes of steel slags, such as pressurized hot stuffy method, the atmospheric tank hot stuffy method, the drum method, etc., and focuses on the reduction and iron extraction of steel slag, the preparation of high value-added materials with steel slag as raw materials, and the waste heat recovery of high-temperature steel slag. It is pointed out that the resource utilization of steel slag not only includes the recovery and utilization of materials, but also the recovery of heat energy contained in steel slag. At the goal of "double carbon", we should pay attention to and strengthen the full quantitative recovery and utilization of metal iron, tailings and heat energy in molten steel slag, so as to truly help achieve the goal of "double carbon".